2003
DOI: 10.1152/jn.01105.2002
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Neural Networks With Transcranial Magnetic Stimulation Applied Over the Dorsal Premotor and Primary Motor Cortices

Abstract: . Modulating neural networks with transcranial magnetic stimulation applied over the dorsal premotor and primary motor cortices. J Neurophysiol 90: 1071-1083, 2003; 10.1152/jn.01105.2002. Our study uses the combined transcranial magnetic stimulation/positron emission tomography (TMS/PET) method for elucidating neural connectivity of the human motor system. We first altered motor excitability by applying low-frequency repetitive TMS over two cortical motor regions in separate experiments: the dorsal premotor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
123
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 81 publications
18
123
3
5
Order By: Relevance
“…While other studies found effects with a delay of several minutes after cessation of the rTMS train (Chouinard et al, 2003;Johnson et al, 2007), we did not find significantly changed rCBF at later time points, as revealed by whole-brain analyses. One possible explanation is that in the former study a different brain region was stimulated (the left primary and premotor cortex) while in the latter study behavioral effects and not rCBF were reported after low frequency rTMS of the left DLPFC.…”
Section: Discussioncontrasting
confidence: 99%
“…While other studies found effects with a delay of several minutes after cessation of the rTMS train (Chouinard et al, 2003;Johnson et al, 2007), we did not find significantly changed rCBF at later time points, as revealed by whole-brain analyses. One possible explanation is that in the former study a different brain region was stimulated (the left primary and premotor cortex) while in the latter study behavioral effects and not rCBF were reported after low frequency rTMS of the left DLPFC.…”
Section: Discussioncontrasting
confidence: 99%
“…Compensatory mechanisms involving the recruitment of other parts of the motor system could, however, have masked interference with response execution (Lee et al, 2003). Indeed, coactivation and/or inhibition of topographically and functionally related regions, such as the dorsal premotor cortex (PMd), supplementary motor area (SMA), cingulate motor cortex, thalamus, putamen, and contralateral M1 (Chouinard et al, 2003;Bestmann et al, 2004), are possible because TMS induces effects proximal and distal to the site of stimulation (Hallett, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…rTMS of the left M1 affects motor-related regions of the brain (7,8,(41)(42)(43)(44)(45)(46); therefore, we acquired images covering these regions with an axial field of view of 40 mm from the top of the brain surface. DWI was performed with a twice refocused spin-echo echo-planar imaging sequence sensitized to diffusion by an interleaved pair of bipolar magnetic field gradient pulses (16).…”
Section: Methodsmentioning
confidence: 99%